Akibat Hukum Pencairan Kredit Yang Didasarkan Pada Covernote Notaris - Silvia Anggraini Yusmi (Magister Kenotariatan, Universitas Jambi, 2020)
The purpose of this study is to examine and analyze the legal consequences of credit disbursement based on covernote notaris. This type of research used in this study is normative juridical research using the law approach, conceptual approach, and case approach. The results of Covernote's research made on the basis of an agreement between the Notary and the Bank in disbursing credit are valid, but only have a position as a statement from the notary and have no legal power because there is no Notary's authority in making a Government. The legal consequence of credit disbursement based on Notary covernote is that if the management of mortgage rights cannot be completed in accordance with the covernote made by the Notary Public, the object of collateral in the mortgage agreement cannot be executed immediately or the mortgage agreement is null and void while the credit agreement has not yet ended. Covernote Notary does not have the legal power to provide legal protection for banks as creditors in credit agreements in the event of defaults during the process of assigning collateral rights. The notary can be held liable for his mistakes if in the issuance of the covernote there are elements which contain incorrect information about the contents of the covernote. Keywords: Covernote, Notary, Banking